SEXUAL VIOLENCE, BULLYING, AND RECOVERY MANAGEMENT IN AN ISLAMIC EDUCATIONAL ENVIRONMENT: CHALLENGES IN THE ERA OF DISRUPTION - Khafidhotun Nasikhah; Singgih Aji Purnomo; Sri Rahmawati (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
Violence must not be normalised. The phenomena of sexual violence and bullying in Islamic educational institutions are serious problems that require not only preventive measures but also an effective recovery management system. This study aims to analyse the implementation of recovery management for victims of sexual violence and bullying in Islamic educational institutions, as well as to formulate a Collaborative Recovery Management model from the perspective of Islamic Educational Management. This study employs a descriptive qualitative approach, using survey data collected from institutional leaders, teachers, students, and parents. Data were collected via open-ended questionnaires and analysed using thematic analysis through the processes of data reduction, coding, categorisation, interpretation and triangulation. The results indicate that recovery management has shifted from a reactive approach to a more integrated system involving institutional protection, psychosocial support and collaboration amongst educational institutions, families and the community. School administrators have implemented mechanisms for reporting, victim protection, confidentiality, parental involvement and the enforcement of sanctions, whilst teachers act as initial counsellors, providing emotional support, early identification and ongoing monitoring. Students feel a sense of safety not only through the existence of rules but also through supportive relationships with teachers and peers. However, the normalisation of verbal bullying, low rates of victim reporting, inconsistent teacher competencies and limited access to professional psychological services are still observed. This study concludes that effective recovery management requires the integration of institutional governance, psychosocial recovery, and collaboration amongst all stakeholders. Therefore, this study proposes a Collaborative Recovery Management model as a conceptual contribution to strengthening the system for recovery from violence in Islamic educational settings.